Current State and General Perceptions of the Use of Extended Reality (XR) Technology at the University of Newcastle: Interviews and Surveys From Staff and Students. (April 2022) - Kluge, Murielle G.; Maltby, Steven; Keynes, Angela; Nalivaiko, Eugene; Evans, Darrell J. R.; Walker, Frederick R.
Extended reality (XR) technology is an emerging teaching tool within the higher education sector. Many institutions are currently running pilot projects, primarily assessing individual XR teaching tools typically being led by innovative/technology-driven teaching staff, which may introduce a self-selection bias and may not represent the general attitudes of the broader staff and student population. We applied a mixed-methods approach to gain insight into end-user acceptability, value areas, barriers, and opportunities for the adoption of XR in teaching at an Australian University. A university-wide online survey and targeted interview sessions with XR technology users show a general readiness for broad adoption of XR technologies in university education. Whilst existing XR teaching applications were described as "successful, " relatively few applications were sustainably integrated into the curriculum. Our data highlights the existing barriers for the successful transition from individual use-cases of XR tools to broader adoption across university institutions.